Empowering natural killer cells to combat acute myeloid leukemia: perspective on CAR-NK Cell therapy - Gierschek, Fenja; Schlueter, Juliane; Kühnel, Ines; Feigl, Frederik Fabian; Schmiedel, Dominik; Prüfer, Maren; Buchinger, Leon; Cerwenka, Adelheid; Cappel, Claudia; Huenecke, Sabine; Köhl, Ulrike; Wels, Winfried S.; et al. (Transfusion medicine and hemotherapy, 2024)
Background: Acute myeloid leukemia (AML) is an aggressive hematologic malignancy with a high relapse rate and still limited therapeutic options. Natural killer (NK) cell-based immunotherapy has the potential to improve outcomes for patients with AML. Summary: Recent preclinical studies and early-stage clinical trials aim to enhance the intrinsic anti-leukemic properties of NK cells by selectively targeting AML cells with chimeric antigen receptors (CARs). Furthermore, NK and CAR-NK cells can be combined with other therapeutic modalities or engineered further to overcome the immunosuppressive microenvironment, and treatment resistance of AML blasts and leukemia-initiating cells (LIC). Key Messages: In this review, we summarize preclinical studies with cytokine-stimulated or genetically engineered NK cells derived from different cell sources for the treatment of AML and their translation into early-phase clinical trials. We also provide an overview of promising recent developments toward innovative NK cell-based therapies that may be implemented in the near future.
Gesehen am 07.01.2025